2021
DOI: 10.3390/ijms22083908
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Enhances the GABAergic Synaptic Activities on the Hypothalamic Preoptic Area (hPOA) Neurons

Abstract: Lithium (Li+) salt is widely used as a therapeutic agent for treating neurological and psychiatric disorders. Despite its therapeutic effects on neurological and psychiatric disorders, it can also disturb the neuroendocrine axis in patients under lithium therapy. The hypothalamic area contains GABAergic and glutamatergic neurons and their receptors, which regulate various hypothalamic functions such as the release of neurohormones, control circadian activities. At the neuronal level, several neurotransmitter s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…These findings suggest that excitotoxicity could be one of the mechanisms by which lithium can cause adverse effects. On the other hand, the effects of lithium on GABAergic signaling are also known to affect the release of glutamate and dopamine [90]. In the brains of rats, chronic lithium use significantly upregulated the levels of glutamic acid decarboxylase and gamma globulin (GABA) and decreased the concentration of dopamine [86].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that excitotoxicity could be one of the mechanisms by which lithium can cause adverse effects. On the other hand, the effects of lithium on GABAergic signaling are also known to affect the release of glutamate and dopamine [90]. In the brains of rats, chronic lithium use significantly upregulated the levels of glutamic acid decarboxylase and gamma globulin (GABA) and decreased the concentration of dopamine [86].…”
Section: Discussionmentioning
confidence: 99%
“…Yet to date, the precise pharmacodynamics of lithium regarding BD is not completely elucidated [ 66 ]. Nevertheless, recent studies reported that Li persuades various biochemical processes at the cellular level through the modulation of neurotransmission [ 67 , 68 ].…”
Section: Reviewmentioning
confidence: 99%
“…Li + decreases excitatory neurotransmission at the cellular level by lowering dopamine and glutamate levels. It increases inhibitory transmission by increasing GABA and serotonin levels [ 66 , 67 ]. Li + increases GABA levels, thus directly activating GABA receptors and additionally reducing glutamate and down-regulate N-methyl D-aspartate (NMDA) receptors [ 66 , 69 ].…”
Section: Reviewmentioning
confidence: 99%
“…It also decreases excitatory neurotransmission at the cellular level by modulating neurotransmitter (dopamine and glutamate) levels [ 2 ]. It increases inhibitory transmission by increasing GABA and serotonin levels [ 6 ]. Lithium also downregulates N-methyl D-aspartate (NMDA) receptors [ 7 ].…”
Section: Introductionmentioning
confidence: 99%